[11C]MPC‐6827: A microtubule‐based pet imaging tracer for AD and related dementias: Neuroimaging / animal imaging. (7th December 2020) - Macauley‐Rambach, Shannon; Damuka, Naresh; Whitlow, Christopher T.; Mintz, Akiva; Craft, Suzanne; Sai, Kiran Solingapuram
Abstract: Background: Loss of microtubule (MT) network and impairment of MT function are considered to be part of pathophysiology of several CNS disorders, including AD, Parkinson disease and other ADRS and tauopathies. A BBB penetrating MT‐based PET ligand would permit imaging a variety of CNS disorders. Our lab reported the first brain‐penetrant PET radiotracer [ 11 C]MPC‐6827 to image MTs in vivo, in both wild and transgenic AD mice. Here, we report a pilot longitudinal [ 11 C]MPC‐6827 PET imaging study with early, middle and late stages of Aβ and tau progression in APP/PS1 and P301S mice respectively. PET imaging in NHP brains was performed to test translational utility. Method: Dynamic brain microPET/CT imaging was performed with [ 11 C]MPC‐6827 in APP/PS1 mice at 3, 18 and 22 months and in P301S mice (n=4) at 5, and 10 months. Regions of interests (ROIs) were drawn in whole brain, cortex, cerebellum and hippocampus and time‐activity curves (TACs) were determined. Basic distribution volume ratios (DVRs) between high‐ and low‐uptake regions were calculated. Dynamic 2h PET/CT imaging was performed in adult male vervet monkeys (n=8). Result: Based on ROIs and TACs in whole brain, cortex and hippocampus, the radioactive uptake of 3 month‐old TG APP/PS1 mice was ∼30% higher compared to the uptake at 18 months, which in turn was ∼18% higher over 22 month‐old mice. Radioactive uptake of TG P301S mice at 5 months was ∼24% higher compared to 10‐month old mice. DVRs from cortex and hippocampus to cerebellum were ∼2‐fold higher in younger APP‐PS1 and P301S mice compared to their older littermates. Radioactive changes in all experiments were statistically significant, substantiating our preliminary imaging data. NHP‐PET brain analyses indicated brain penetration and high retention of the tracer. Conclusion: [ 11 C]MPC‐6827 demonstrated decreased radioactive uptake with increased brain Aβ and tau loads. A MT‐based PET imaging tracer could be a potential early imaging biomarker for AD and other ADRDs. PET imaging studies in monkey brains showed high BBB penetration. Binding distribution is in good agreement with the known MT‐mice distribution. Next steps are to correlate radioactive uptake with tau pathologies and in an NHP model of AD.